2017
DOI: 10.1108/ijchm-10-2015-0559
|View full text |Cite
|
Sign up to set email alerts
|

The effects of festival attendees’ experiential values and satisfaction on re-visit intention to the destination

Abstract: Purpose The purpose of this study was first to examine how goal-oriented attendees and experiential-oriented attendees were related with their overall satisfaction and loyalty of the destination with respect to international food and wine festival. It also investigated how these relations are mediated by different dimension of experiential consumption values such as consumer return on investment (CROI, active value), escapism (active value) and service excellence (reactive value) and aesthetics (reactive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 76 publications
4
70
0
3
Order By: Relevance
“…Finally, Alderighi, Bianchi, and Lorenzini, (2016) also indicate that previous experience with local food specialities is positively related to the intent to revisit a destination, Ji, Wong, Eves, and Scarles (2016) confirm a direct positive impact of food satisfaction on tourist loyalty (revisit intention and WOM), and Lee, Sung, Suh, and Zhao (2017) find that satisfaction with a food and wine festival had a positive effect on attendee intention to revisit the destination.…”
Section: Tourist Gastronomy Experiencesmentioning
confidence: 88%
“…Finally, Alderighi, Bianchi, and Lorenzini, (2016) also indicate that previous experience with local food specialities is positively related to the intent to revisit a destination, Ji, Wong, Eves, and Scarles (2016) confirm a direct positive impact of food satisfaction on tourist loyalty (revisit intention and WOM), and Lee, Sung, Suh, and Zhao (2017) find that satisfaction with a food and wine festival had a positive effect on attendee intention to revisit the destination.…”
Section: Tourist Gastronomy Experiencesmentioning
confidence: 88%
“…Previously, scholars have conducted a number of studies to better understand the role of food consumption for tourists including food experiences in various festivals [15][16][17], food travel for experiencing local island foods [18,19], and urban tours for food [20][21][22]. Particularly, previous research on street foods have been mainly focused on the food safety for public health issues such as hygiene or disease from street foods [23][24][25] and the traveler's knowledge of street foods [26].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically to beverage tourism, many studies investigating its economic effects highlight positive relationships between this and other types of tourism, such as cultural and heritage tourism (Bruwer & Johnson, 2010; W. Lee et al, 2017). For instance, research on wine tourism shows how local communities and authorities use wine to promote themselves across different tourism networks and segments, strengthening brand identities related to specific wines and defined geographic areas too (Bruwer & Johnson, 2010; Charters & Ali‐Knight, 2002; Velikova, Slevitch, & Mathe‐Soulek, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, several empirical studies indicated event tourism, the form of tourism associated with specific events such as cultural or gastronomic events (Getz, 2008), as an effective contributor for local economic development due to its potential in terms of creating employment and generating taxation revenues (Balaguer & Cantavella‐Jordá, 2002; Laing, 2018; W. Lee, Sung, Suh, & Zhao, 2017; Tohmo, 2005). Increasingly more cities and towns organize festivals and events to enhance their visibility and improve their image and profile, with the aim of creating a surplus value for resident taxpayers (Backman, 2018; Brännäs & Nordström, 2002).…”
Section: Introductionmentioning
confidence: 99%